2019
DOI: 10.1590/1806-9282.65.7.937
|View full text |Cite
|
Sign up to set email alerts
|

Elderly patients with glioblastoma: the impact of surgical resection extent on survival

Abstract: The information provided through this project must be assessed and criticized by the physician responsible for the conduct that will be adopted, depending on the conditions and the clinical status of each patient. The impact of the neurosurgery in elderly patients with glioblastoma multiforme (GBM) is still unclear. The objective of this systematic review was to evaluate the overall survival of patients over 65 years old submitted to GBM surgical treatment and analyze the rates of postoperative complications i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…Elderly age negatively affected the prognosis only in cases of limited resection, supporting the role of surgery in fit older patients when a safe and large resection can be planned [42][43][44].…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…Elderly age negatively affected the prognosis only in cases of limited resection, supporting the role of surgery in fit older patients when a safe and large resection can be planned [42][43][44].…”
Section: Discussionmentioning
confidence: 87%
“…Age, performance status, extent of surgical resection and MGMT methylation status are well known prognostic factors for GBM patients [4,[21][22][23][24][25][26][27][28][29][30][31][32][33][34][39][40][41][42][43][44]. Nevertheless, the high degree of clinical/molecular heterogeneity found among GBM patients do not generally allow us to correctly classify GBM patients with the use of a single predictor or a few predictors.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, the standard treatment methods are surgery, chemotherapy, and radiation therapy 2 . A recent study found that surgical resection extent in elderly patients with glioblastoma has an impact on survival 3 . In recent years, researchers have been working to explore the molecular mechanisms of gliomas, discovering telomerase reverse transcriptase and many other molecules 4, 5 .…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have shown that, in addition to conventional prognostic factors, the molecular profile of tumors can be used to select from these treatment alternatives. [3][4][5][6][7][8][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29] Microsurgery's place within this framework remains unclear. 6,[18][19][20][21][22] Even though gross total resection (GTR) has been proven to increase OS, little data are available concerning the risks and benefits of resections in older adults.…”
Section: Introductionmentioning
confidence: 99%
“…[3][4][5][6][7][8][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29] Microsurgery's place within this framework remains unclear. 6,[18][19][20][21][22] Even though gross total resection (GTR) has been proven to increase OS, little data are available concerning the risks and benefits of resections in older adults. 8,[11][12][13][14][15][16][17][18] This retrospective study by 2 neuro-oncology centers has been performed to assess the prognostic profile, clinical outcome, treatment-associated morbidity, and treatment burden of elderly patients with newly diagnosed GBM, who were found eligible for elective tumor resection as part of contemporary management.…”
Section: Introductionmentioning
confidence: 99%